Analysis and Measurement of Scientific Collaboration Networks Performance - Imam Much Ibnu Subroto; Sam Farisa Chaerul Haviana; Wiwiek Fatmawati (IAES Indonesian Section, 2020)
Collaboration of scientific research among researchers or universities is very important especially to improve the quality and quantity of the research. It gives the positive impact and very beneficial for both parties so this scientific research network becomes an important component in measuring performance and ranking institutions for national and international levels. The interviews result show that the amount of collaboration alone cannot fair to be used as performance measurement, because in general the successful collaboration can be established to other institutions with higher ranks, which will give a good quality impact to the institution. The purpose of this paper is to propose a new performance measurement formula using case studies in Indonesia. Scientific collaboration networks are generated based on data from lecturers and institutions, especially research outputs indexed in the SINTA-Science and Technological Index. SINTA is the largest and most comprehensive portal for measuring research performance in Indonesia. The formula proposed in this research is to consider the number and weighting based on the score of the institution in the previous year to calculate a new score of the performance of the scientific collaboration network. Implementation results show that Riau Province has the highest collaboration score at the regional level, while the Bandung Institute of Technology as an institution with a score of 46.563 is the highest at the institutional level